Imaginário e ideologia cristã: uma versão portuguesa do além medieval na visão de Túndalo (século XV). - OLVEIRA, Solange Pereira (2014)
The objective of this study is to analyze the ideological implications of the Church in the construction of the spaces beyond the tomb. Our problem focuses on the stories of the imaginary addition that was widely publicized in medieval society travel. We use in this research the Vision of Tngudal, an example of a imaginary voyage to Beyond, produced in the twelfth century. We refer to the Portuguese versions of the XIV-XV centuries this work, we intend to analyze the ideological discourse of the Catholic Church on the spaces of the underworld (Hell, Purgatory and Paradise) in an attempt to strengthen its role in the medieval world. Thus, the problem that motivates this research is grounded in the Christian ideology and the imaginary spaces of the Grave Beyond the oratores so widespread in the Middle Ages, which certainly contributed to the process of Christian evangelization. And to understand the power range of this institution in the social life of the people in Middle Ages are worth the evidence offered in the Vision of Tnugdal that guide us in this proposed research topic.